Innovation In Quran Memorization Learning For Deaf Children: An Inclusive Approach - Furqan; Insani, Andi Nur; Mukhlishin; Muhammad Iksan; Bohari Muslim (Universitas Muhammadiyah Makassar, 2025)
This study aims to examine the effectiveness of the Abata Method in enhancing Quran memorization skills among deaf children with special needs at SLB Negeri Pembina, West Sulawesi Province. The Abata Method, which integrates a Visual Phonetic approach, is designed to assist deaf children in reading and memorizing the Quran by utilizing lip vibrations and hand movements. This research employs a descriptive qualitative method, with data collected through interviews, observations, and documentation. The results indicate that the implementation of the Abata Method has successfully improved Quran memorization skills among deaf children, despite some inhibiting factors such as fluctuations in children's enthusiasm and mood, as well as the limited availability of speech therapists. With support from teachers and parents, the children can gradually memorize the Quran without rigid targets. These findings are expected to contribute to the development of inclusive education curricula in Indonesia and support the goal of equitable access to education for children with special needs.